2008
DOI: 10.1021/jp709846s
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Structural, Acidic and Hydrophilic Properties of Sn−BEA with Ti−BEA Using Periodic Density Functional Theory

Abstract: Periodic density functional theory has been employed to characterize the differences in the structural, Lewis acidic and hydrophilic properties of Sn-BEA and Ti-BEA. We show that the incorporation of Sn increases the Lewis acidity of BEA compared to the incorporation of Ti. Hence, the present work gives insight into the role of Sn in increasing the efficiency of the oxidation reactions. The results also justify that the percentage of Sn substituted in BEA is less than Ti. The structural analysis shows that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 76 publications
10
49
0
Order By: Relevance
“…[33][34][35][36] Similar to previous studies, [37][38][39][40] the periodic model of BEA zeolite corresponded to polymorph A. [41] The optimized parameters of the tetragonal BEA unit cell were a = b = 12.657 and c = 26.396 .…”
supporting
confidence: 65%
“…[33][34][35][36] Similar to previous studies, [37][38][39][40] the periodic model of BEA zeolite corresponded to polymorph A. [41] The optimized parameters of the tetragonal BEA unit cell were a = b = 12.657 and c = 26.396 .…”
supporting
confidence: 65%
“…Li et al (15) came to an analogous conclusion when a similar Lewis acid strength order of Ti < Zr ≤ Sn was found when computationally evaluating COE-4 (delaminated FER topology) zeolites using probe molecule adsorption energies. Although several theoretical studies have been conducted on the topic (16,17), few comprehensive experimental studies quantify Lewis acidity across different heteroatoms. To this end, Gunther et al, using magic angle spinning (MAS) nuclear magnetic resonance (NMR) of 15 N pyridine adsorbed on M-Beta zeolites, found that the experimentally observed 15 N chemical shift provides a scale for Lewis acidity that correlates well with Mulliken electronegativities and pyridine adsorption energies, as seen in Figure 2 (W.R. Gunther, V.K.…”
Section: Quantifying Lewis Aciditymentioning
confidence: 99%
“…These catalytic materials are expected to exhibit the hydrophobic nature as water present is responsible in poisoning the active site. Discrepancy in calculation of the adsorption energy of water molecule on Sn-and Ti-BEA zeolite is already reported by us in our earlier study [34]. We next analyze the convergence of total energy and the desired properties dependent on it as a function of plane wave cut-off.…”
Section: Results and Discussion: Role Of Plane Wave Cut-off In Structmentioning
confidence: 63%
“…There are nine distinct crystallographically defined T-sites. We adopt the structure of BEA from our earlier theoretical study [34] and incorporate the Sn-and Ti-atoms at T2 and T1 sites [42], respectively. The interaction of H 2 O molecule at the active site is very important since it gives rise to geometric perturbations and energetic differences.…”
Section: Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation